(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The research question is why poor education is one of the main social determinants of health, as is poverty and social exclusion? The theoretical hypothesis is that education contributes to defining people’s lifestyle or habitus. Education allows to build character skills (elements of habitus), such as conscientiousness, emotional stability, openness to experience, perseverance, responsibility. In complex adaptive health systems, the multiple interactions and relationships between people and elements of the system mean that character skills are strategic.